Pengaruh Financial Literacy, Trus Dan Image Terhadap Behaviour Intention To Use Fintech (Studi Pada Mahasiswa Prodi Manajemen Angkatan 2018 Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Retno Damayanti; Nurhidayah Nurhidayah; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of Financial Literacy, Trust and Image on Behavior Intention to use Fintech in Management Study Program Students Class of 2018 Faculty of Economics and Business, Islamic University of Malang. Methods of analysis using multiple linear regression analysis. The population in this study were Active Students of Management Study Program Class of 2018 Faculty of Economics and Business, Islamic University of Malang, which was obtained as many as 518 students. In this study, the sample selection used the Slovin formula with purposive sampling technique, in order to obtain 84 students who met the criteria. The results of this study indicate that (1) Financial Literacy has no significant effect on Behavior Intention to use Fintech, (2) Trust has a significant and positive effect on Behavior Intention to use Fintech, (3) Image has a significant and positive effect on Behavior Intention to use Fintech. . Keywords : Financial Literacy, Trust, Image, Behavior intention to use Fintech.